Penal Substitutionary Atonement and the Problem of Shame in Addiction - Carlier, Jennifer (Pastoral psychology, 2023)
Penal substitutionary atonement (i.e., the notion that Jesus Christ died on the cross to bear the burden of punishment for sin in our place) is a profoundly harmful theology for those suffering from addiction because it exacerbates the sufferer's sense of shame and thus keeps them trapped in the very shame-driven addiction cycle from which they need redemption. Shame is a core problem in addiction in that it often both causes and perpetuates the addiction cycle. That is, people with substance use disorders often use to escape feelings of shame momentarily. However, the use itself often becomes its own source of shame. This generates an addiction cycle in which a person uses to escape shame, only to feel more shame after using, and then uses again to escape that shame. Recovery from addiction therefore requires interventions that free the person suffering from the bondage of shame. Paradoxically, penal substitutionary atonement - a common version of the theological doctrine most suited to the search for freedom from bondage (i.e., salvation) - is often seen as a significant impediment to the pursuit of freedom from the bondage of addiction. A central claim of the theory of penal substitutionary atonement is that we are freed from the bondage of sin through Christ's atoning death. Yet, rather than offering freedom from bondage, penal substitutionary atonement keeps the person with addiction mired in the very shame from which they need freedom by relying on a judicial metaphor, which identifies the divine-human relationship as one between judge and, at best, a forgiven criminal.